Effects of oxygen species from Fe addition on promoting steam reforming of toluene over Fe–Ni/Al2O3 catalysts. (26th October 2016) - Hu, Song; He, Limo; Wang, Yi; Su, Sheng; Jiang, Long; Chen, Qindong; Liu, Qicong; Chi, Huanying; Xiang, Jun; Sun, Lushi
Abstract: A series of Fe-modified Ni/Al2 O3 (FNA) catalysts with different Fe/Ni ratios (Fe/Ni = 0.5, 2, 3) was investigated during steam reforming of toluene as a model compound of biomass tar. The percentages of hydrogen in the product gas reached about 65% over prepared catalysts. The addition of Fe remarkably increased the toluene conversion and reduced the amount of coke. According to X-ray photoelectron spectrometer and pulse injection experiments, the addition of Fe increased the amount of lattice oxygen and adsorbed oxygen on the surface of FNA. The Fe in alloy was easily oxidized to FeOx by steam. The lattice oxygen in FeOx could oxidize the carbon deposited or intermediates on adjacent Ni atoms to produce CO. Meanwhile, the more adsorbed oxygen promoted the further reaction with the intermediates during the steam reforming of toluene. Both the adsorbed oxygen and lattice oxygen from the addition of Fe played important roles in the steam reforming of toluene. For the two types of cokes (amorphous/paraffinic and graphitic/filamentous), the formation of graphitic/filamentous carbon was remarkably suppressed due to the oxidization property of oxygen species from the addition of Fe. Highlights: The addition of Fe increased the amount of lattice oxygen and adsorbed oxygen. The lattice oxygen in FeOx oxidized carbon deposition or intermediate on Ni atom. The more adsorbed oxygen promoted the further reaction of intermediate. Sufficient oxygen decreased coke by limiting graphitic/filamentous carbon.